Analysis of Seagress Vegetation in Soop Village, Sorong Islands District, Sorong City - Ferni S Imbir; Melisa Masengi; Roger R. Tabalessy; Yacob Maryen; Dwi Indah Widya Yanti (INTEGRATED OF FISHERIES SCIENCE, 2025)
Seagrasses are flowering plants (Angiospermae) that grow in shallow marine environments and possess rhizomes, leaves, flowers, and fruits similar to vascular plants on land. This study aimed to identify seagrass species, analyze vegetation conditions including frequency, density, and cover of each species, and examine factors affecting seagrass growth in the coastal area of Soop Village, Sorong Islands District, Sorong City, West Papua. The research was conducted from August to October 2014 using the line transect method with 50 cm x 50 cm quadrats placed systematically along two transects (each 250 m long). Data were analyzed using calculations of frequency, density, cover, and the Important Value Index (IVI). The results revealed three seagrass species: Enhalus acoroides, Cymodocea rotundata, and Syringodium isoetifolium. The relative frequency values were 54%, 26%, and 20% respectively; relative density values were 68%, 16%, and 16%; and relative cover values were 54%, 26%, and 20%. Enhalus acoroides dominated the community with an IVI of 176%. Based on the Decree of the Minister of Environment Number 200 of 2004, the seagrass meadow condition was classified as unhealthy to poor due to anthropogenic pressures such as tourism activities, boat mooring areas, indiscriminate anchoring, and domestic waste disposal. Management efforts including waste bin provision, boat mooring area regulation, and banning of environmentally damaging fishing gear are necessary to restore the seagrass ecosystem